Pelatihan Pembuatan Sabun Cuci Tangan Alami ‘Clitoria Nature’ dari Bunga Telang di MTsN 1 Kota Palangka Raya - Amanda Indriani; Jumrodah Jumrodah (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Hand hygiene is an essential step in preventing the transmission of infectious diseases, making the availability of safe and environmentally friendly hand soap an important necessity in daily sanitation practices. This community service activity aims to enhance students’ environmental literacy, technical skills, and ecological awareness through training on producing natural hand soap based on butterfly pea flower (Clitoria ternatea) extract, with the final product named Clitoria Nature. The program was implemented using the Participatory Action Research (PAR) method, which consists of four stages planning, action, observation, and reflection—through strategies including socialization, demonstration, and hands-on practice. The subjects of this activity were 32 students of Grade VIII Room 1 at MTsN 1 Palangka Raya City. The results showed an increase in students’ understanding of the benefits of natural ingredients, their ability to formulate liquid soap, and the development of behavior that favors the use of natural hygiene products. Theoretically, the anthocyanin and flavonoid content of butterfly pea flowers supports the antibacterial potential of the formulated soap. This program not only produced an environmentally friendly hand soap but also contributed to the formation of healthier and more sustainable sanitation behaviors.